Pathological features of the placenta in hypothyroidism during pregnancy: a population-based retrospective cohort study in Chinese population - Bao, Zhuo; Li, Yingbin; Xue, Tong; Liu, Yixuan; Yan, Jinxiang; Wang, Xiaoqian; Li, Yunling; Zeng, Xianxu; Zhao, Chengquan; Guo, Yongzhen; Lei, Dongmei (Frontiers in Endocrinology, 2025)
BackgroundPregnant women, due to changes in their metabolic and immune states, are a high - risk group for thyroid diseases. The most common one among them is hypothyroidism. However, there are few reports on its impact on placental morphology. This study aims to assess the effect of hypothyroidism on the gross morphology and histopathology of the placenta compared with gestational age - matched controls.MethodsPlacental samples from women with singleton pregnancies who gave birth at the Third Affiliated Hospital of Zhengzhou University from June 2022 to December 2023 were collected. A total of 852 participants were recruited according to the inclusion and exclusion criteria, with 213 in the hypothyroidism group and 639 in the control group. Baseline demographic and clinical data of the pregnant women, as well as neonate-related information, were recorded. Gross placental measurements and histological sections from standardized placental samples were evaluated and statistically analyzed.ResultsOverall, compared with the control group, insufficient vascular perfusion and inflammation were more frequently observed in the placentae of pregnant women with hypothyroidism. These included retroplacental hemorrhage (4.69% versus 1.25%, P = 0.002) related to maternal vascular malperfusion, delayed villous maturation (30.52% versus 17.37%, P<0.001) and decreased vasculosyncytial membrane (32.39% versus 24.10%, P = 0.017) related to fetal vascular malperfusion, chronic chorioamnionitis (7.04% versus 1.56%, P<0.001), and villitis of unknown etiology (3.29% versus 0.94%, P = 0.016). Additionally, hypothyroidism increased the risk of fetal complications, including fetal distress (15.49% versus 9.68%, P = 0.024) and small for gestational age (8.45% versus 4.54%, P = 0.030).ConclusionGestational hypothyroidism can lead to histopathological abnormalities in the placenta. These abnormalities affect the development and function of the placenta, consequently influencing perinatal outcomes and fetal development.